2012
DOI: 10.2136/sssaj2012.0273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulch Cover Rate on Interrill Erosion Processes and the Size Selectivity of Eroded Sediment on Steep Slopes

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher. Effects of Mulch Cover Rate on Interrill Erosion Processes and the Size Selectivity of Eroded Sediment on Steep Slopes Soil & Water Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 50 publications
5
73
1
1
Order By: Relevance
“…Gholami et al (2013) studied straw mulching effect on sediment yield from eroded plots and showed that the straw mulch had a significant effect in changing soil erosion characteristics at a confidence level of 99 %. Shi et al (2013) verified the positive effects of mulch cover on reduction of soil loss. Fernandez and Vega (2014) investigated the effects of straw mulch on erosion control after wildfire and showed that the straw mulch could decrease soil erosion.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Gholami et al (2013) studied straw mulching effect on sediment yield from eroded plots and showed that the straw mulch had a significant effect in changing soil erosion characteristics at a confidence level of 99 %. Shi et al (2013) verified the positive effects of mulch cover on reduction of soil loss. Fernandez and Vega (2014) investigated the effects of straw mulch on erosion control after wildfire and showed that the straw mulch could decrease soil erosion.…”
Section: Introductionmentioning
confidence: 61%
“…The result comparison showed that the straw mulch was effective in reducing runoff toward two other amendments (Smets et al, 2008;Shi et al, 2013). This amendment could be more effective at rainfall intensity of 30 mm h −1 .…”
Section: Runoffmentioning
confidence: 95%
See 2 more Smart Citations
“…However, soil surface properties can also influence the process of selectivity. The influence of a range of soil surface properties including texture, organic matter content, vegetative cover and slope gradient on both particle size distribution and organic matter composition of eroded material have been investigated (Quinton et al 2001;Defersha and Melesse 2012;Shi et al 2013;Chartier et al 2013). Information on the selectivity of interrill erosion processes is needed as input for watershed management tools including sediment budgets and the assessment of geomorphic connectivity, as fine-grained and organic-rich particles can have different patterns of erosion, transport and deposition .…”
Section: Introductionmentioning
confidence: 99%